2014
DOI: 10.1111/socf.12103
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Privilege: Trans Men, Masculinities, and Changing Perceptions of Safety

Abstract: This article examines the construction of masculinities in social interaction through in-depth interviews with trans men living in the San Francisco Bay Area. Interviewees' concerns for safety, particularly the threat of violence from other men, shaped their masculine practices, which led some men to practice defensive masculinities and, for others, constrained their ability to practice transformative masculinities. Respondents' concerns for safety, and their masculine practices, changed according to variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
1
39
0
4
Order By: Relevance
“…When taking into account the Facebook shares and Facebook friends, trans men overall raised more money and a higher percentage than trans women. These findings may be reflective of the relative degree of social privilege afforded to some (passing, normatively masculine) transgender men through sexism 37 and transmisogyny. 38 However, when comparing trans men and trans women with an equal number of Facebook shares, trans women raised more money.…”
Section: Discussionmentioning
confidence: 90%
“…When taking into account the Facebook shares and Facebook friends, trans men overall raised more money and a higher percentage than trans women. These findings may be reflective of the relative degree of social privilege afforded to some (passing, normatively masculine) transgender men through sexism 37 and transmisogyny. 38 However, when comparing trans men and trans women with an equal number of Facebook shares, trans women raised more money.…”
Section: Discussionmentioning
confidence: 90%
“…In light of the evidence that fear and perception of safety can alter women's behavior, it may seem natural that trans* individuals also engage in similar avoidance and defensive behavior in reaction to evaluations of safety. In fact, one study has shown how trans men feeling a lack of safety are compelled to alter their behavior, to perform defensive masculinities that uphold the gender binary (Abelson 2014). These dynamics are also likely to extend to how trans* individuals intellectually interpret, and emotionally and behaviorally react to their experiences on public transit.…”
Section: Gender and Public Spacementioning
confidence: 99%
“…In this sense, though there are already a number of studies about trans men (Green 2005), not many have discussed the problem of masculinities as constructed by csmm. We know that trans men's masculinities may be seen as contingent ( Blackwood 2009), defensive or constrained (Abelson 2014), hyper-masculine, women-hating and aspiring to the patriarchal hegemonic pattern (quite evident in trans exclusionary feminists; see Raymond 1979;and Jeffreys 2014) or, conversely, feminist (Hines 2002). However, regardless of all the plurality of masculinities enacted by trans men (and non-trans men), which has been portrayed in the studies of Devor (1997), Rubin (2003, Vidal-Ortiz (2002) or Green (2005), among others (Aboim 2016), there is still a gap to be bridged.…”
Section: Introductionmentioning
confidence: 99%